ANALISIS KIMIA 8 JENIS KAYU DARI INDONESIA BAGIAN TIMUR (Chemical analysis of 8 wood species from East Indonesia) - Djeni Hendra (Jurnal Penelitian Hasil Hutan, 1993)
This paper deals with chemical analysis of eight wood species from East Indonesia i. e : Podocarpus imbricatus BL, Pouteria firma Baohani, Phylocladus hypopyllus Hoof.f, Agthis philipinensis Warb, Dacrydium beccarii Parl, Tristania maingayi Duthie, Castanopsis javanica A.DC and Shorea sp. The analysis comprised of the determinations of cellulose, lignin, pentosan, moisture, ash.silica and the solubility in cold water, hot water, sodium hydroxide (1 %), alcohol benzene (I :2).The result shows that cellulose content ranges from 47,58, to 59, 74 percent. The highest cellulose content was obtained from Agathis philippinensis Hooff and low cellulose content from Tristania maingayi Duthie. Lignin content ranges from 25,22 to 29, 84 percent where the highest was obtained from Shorea sp and the lowest from Pouteria firma Baohni and Phylocladus hypophyllus Hoof.f pentosan from 10,84 to 19,66 percent. Moisture content ranges from 10,09 to 13, 70 percent, ash content from 0,13 to 0, 78 percent, silica content from 0,12 to 0,40 percent. Solubility in cold water ranges from 2,11 to 12,97 percent.solubility in hot water from 3,09 to 14,76 percent, solubility in sodium hydroxide (1 %) from 10,65 to 27,68 percent and solubility in alcohol benzene (1:2) from 1,84 to 8,89 percent.